Unexpected binding of an octapeptide to the angiotensin II receptor. - Soffer, R L (1987)
An octapeptide, TBI-22 (Lys-Gly-Val-Tyr-Ile-His-Ala-Leu), inhibited binding of angiotensin II by a solubilized angiotensin receptor partially purified from rabbit liver. This inhibition appears to result from competition for binding to the same receptor. Radioiodinated TBI-22, like angiotensin II, bound to the solubilized receptor with an affinity such that the binding was inhibited 50% by unlabeled TBI-22 or angiotensin II at nanomolar concentrations. The binding reaction, like that for angiotensin II, required p-chloromercuriphenylsulfonic acid and was reversed in the presence of dithiothreitol. TBI-22 and angiotensin II share the sequence Val-Tyr-Ile-His; this tetrapeptide alone, however, did not inhibit binding of angiotensin II. Replacement of the tyrosine residue by aspartic acid in TBI-22 greatly reduced the ability of the peptide to compete with angiotensin II for binding, suggesting an important contribution of this residue to the configuration required for recognition by the receptor.